Familial aggregation of systemic lupus erythematosus and coaggregation of autoimmune diseases in affected families - Kuo, Chang-Fu; Grainge, Matthew J.; Valdes, Ana M.; See, Lai-Chu; Luo, Shue-Fen; Yu, Kuang-Hui; Zhang, Weiya; Doherty, Michael (American Medical Association, 2015)
IMPORTANCE: Relatives of patients with systemic lupus erythematosus (SLE) appear to be at higher risk of SLE and other autoimmune diseases, but estimates of individual familial risks are largely unavailable or unreliable. Furthermore, relative contributions of genetic, shared, and unshared environmental factors to SLE susceptibility remain unclear.